Remittance Inflow in Nepal - Bhattarai, Krishna Prasad (KMC Research Journal, 2025)
Remittance has become one of Nepal’s most significant economic lifelines, substantially contributing to national income, employment, household livelihoods, and poverty reduction. Over the past several decades, remittance inflows have steadily increased, making Nepal one of the highest remittance-receiving countries globally in proportion to its GDP. This study examines the multifaceted role of remittances in Nepal’s socio-economic landscape using secondary data collected from Nepal Rastra Bank, the World Bank, the International Organization for Migration, and the Central Bureau of Statistics. It explores historical trends, destination countries for foreign labor migration, and the socioeconomic implications of remittance at the household and national levels. The findings indicate that remittances have enhanced household consumption, access to education and healthcare, gender empowerment, and rural development. However, challenges such as labor market dependency, increased consumption over investment, brain drain, and family separation remain prevalent. The paper concludes by recommending strategies for sustainable remittance utilization, including skill-based foreign employment, financial literacy development, reintegration support for returnees, and promotion of diaspora investment in productive sectors. Overall, the study contributes to a deeper understanding of remittance as a crucial component of Nepal’s long-term development trajectory.